Physiological and transcriptomic analysis of a salt-resistant Saccharomyces cerevisiae mutant obtained by evolutionary engineering - Seyma Hande Tekarslan-Sahin; Ceren Alkim; Tugba Sezgin (Biomolecules & Biomedicine, 2018)
Salt-resistant yeast strains are highly demanded by industry due to the exposure of yeast cells to high concentrations of salt, in various industrial bioprocesses. The aim of this study was to perform a physiological and transcriptomic analysis of a salt-resistant Saccharomyces cerevisiae (S. cerevisiae) mutant generated by evolutionary engineering. NaCl-resistant S. cerevisiae strains were obtained by ethyl methanesulfonate (EMS) mutagenesis followed by successive batch cultivations in the presence of gradually increasing NaCl concentrations, up to 8.5% w/v of NaCl (1.45 M). The most probable number (MPN) method, high-performance liquid chromatography (HPLC), and glucose oxidase/peroxidase method were used for physiological analysis, while Agilent yeast DNA microarray systems were used for transcriptome analysis. NaCl-resistant mutant strain T8 was highly cross-resistant to LiCl and highly sensitive to AlCl3. In the absence of NaCl stress, T8 strain had significantly higher trehalose and glycogen levels compared to the reference strain. Global transcriptome analysis by means of DNA microarrays showed that the genes related to stress response, carbohydrate transport, glycogen and trehalose biosynthesis, as well as biofilm formation, were upregulated. According to gene set enrichment analysis, 548 genes were upregulated and 22 downregulated in T8 strain, compared to the reference strain. Among the 548 upregulated genes, the highest upregulation was observed for the FLO11 (MUC1) gene (92-fold that of the reference strain). Overall, evolutionary engineering by chemical mutagenesis and increasing NaCl concentrations is a promising approach in developing industrial strains for biotechnological applications.